Acculturation and Syndemic Risk: Longitudinal Evaluation of Risk Factors Among Pregnant Latina Adolescents in New York City. Issue 1 (12th December 2017) - Martinez, Isabel; Kershaw, Trace S; Keene, Danya; Perez-Escamilla, Rafael; Lewis, Jessica B; Tobin, Jonathan N; Ickovics, Jeannette R
Abstract : Second generation Latina adolescents experience increases in severity while immigrant Latinas experience decreases in severity for a syndemic comprised of substance use, intimate partner violence and depression during pregnancy and the postpartum period. Abstract: Background: Syndemics are co-occurring epidemics that synergistically contribute to specific risks or health outcomes. Although there is substantial evidence demonstrating their existence, little is known about their change over time in adolescents. Purpose: The objectives of this paper were to identify longitudinal changes in a syndemic of substance use, intimate partner violence, and depression and determine whether immigration/cultural factors moderate this syndemic over time. Methods: In a cohort of 772 pregnant Latina adolescents (ages 14–21) in New York City, we examined substance use, intimate partner violence, and depression as a syndemic. We used longitudinal mixed-effect modeling to evaluate whether higher syndemic score predicted higher syndemic severity, from pregnancy through 1 year postpartum. Interaction terms were used to determine whether immigrant generation and separated orientation were significant moderators of change over time. Results: We found a significant increasing linear effect for syndemic severity over time ( β = 0.0413, P = 0.005). Syndemic score significantly predicted syndemic severity ( β = –0.1390, P ≤ 0.0001), as did immigrant generation ( β Immigrant = –0.1348, P ≤ 0.0001; β 1st Gen = –0.1932, P = 0.0005). Both immigrant generation ( β Immigrant = –0.1125, P = 0.0035; β 1st Gen = –0.0135, P = 0.7279) and separated orientation ( β = 0.0946, P = 0.0299) were significantly associated with change in severity from pregnancy to 1 year postpartum. Conclusion: Pregnancy provides an opportunity for reducing syndemic risk among Latina adolescents. Future research should explore syndemic changes over time, particularly among high-risk adolescents. Prevention should target syndemic risk reduction in the postpartum period to ensure that risk factors do not increase after pregnancy.